Investigation of ambipolar signature in SiGeOI homojunction tunnel FETs. (January 2016) - Hutin, L.; Oeflein, R.P.; Borrel, J.; Martinie, S.; Tabone, C.; Le Royer, C.; Vinet, M.
Abstract: In this paper, we study the ambipolar tunneling signature from the output characteristics of TFETs featuring Si0.8 Ge0.2 homojunctions, which we compare to those measured on conventional MOSFETs and Schottky Barrier FETs. The difference with the former is immediate since a single TFET can display a transistor effect under both pull-up (nTFET) and pull-down (pTFET) biasing conditions. This is however a property shared with SBFETs, in which injection occurs via tunneling through a single carrier Schottky Barrier instead of band-to-band tunneling. Without requiring quantitative considerations on the current levels or transfer characteristics, we find that simply performing the same dual I D – V DS electrical tests while voluntarily "swapping" the S/D terminals unequivocally characterizes TFET operation, even compared to asymmetrically doped SBFETs.